THE NARRATIVE OF THE RUSSIAN LANGUAGE AS PART OF THE RUSSIAN IMPERIAL HUBRIS - Panov, Volodymyr (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2022)
The article is devoted to the question of how the russian language is combined with russian imperialism. The concept of imperial hybris is proposed, which means the nation’s opinion about itself that it is "one level higher" than Others (nations); an opinion based on a sense of pride. Thus, imperialism in its sources is divided into two components: an irrational sense of pride and a rational episteme that should support this sense. The latter is often built around the binary opposition "civilization-barbarism". The self-understanding of the russian language as best language is revealed, which is best expressed in the myth of the "great and mighty". The self-understanding of a language refers to what methods of description and myths a language has for describing itself; or what methods of description and myths the native speaker uses to describe it. Several such myths are analyzed, in particular, Florensky’s theory about the word "truth". It is shown how exactly the Russian language is combined with the russian imperial hybris. In particular, the russian language is woven into a more general narrative about the "Rotting West" (the rational component), in which the russian language is superior to the languages of the Western civilization. Also, myths about the russian language, the purpose of which is to form an opinion about its superiority and a feeling of pride for it (irrational component), thanks to the trope of synecdoche (according to White), convey this pride to representatives of the russian nation (ie, they feed the irrational component). The history of the expansion of the russian language in the russian state is briefly described. It is shown how the perception of the russian language as better leads to the policy of its protection, why this protection is considered especially necessary outside of the russian state, and how the russian language is used to endow the object of intervention with the status of a barbarian.